Aplikasi Sistem Informasi Geografis (SIG) untuk Kajian Banjir di Kota Denpasar - DEWI, NI KOMANG RINI RATNA; NUARSA, I WAYAN; ADNYANA, I WAYAN SANDI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2017)
Application of Geographic Information System (GIS) For Study of Flood in Denpasar City Denpasar city in general situation has flat area, high rain fall intensity and the dominated landuse of settlement. This condition can reduce the catchment area. This leads Denpasar City become potential for the occurrence of flooding. Therefore, it needs to do research about flood occur in Denpasar. The aim of this research is to find out level of flood vulnerability and it’s spatial distribution in Denpasar. Weighting, scoring and overlay method were used in this research. There are six indicators were analyzed using Geographic Information System (GIS) such as landused, rainfall, type of soil, slope, altitute and drainage density. The result of this research is a map of flood vulnerability in Denpasar City. There are four class of flood vulnerability. Total of the area classified as low, medium, high and very high of flood level are 0,225 hectares (0,002%), 251,73 hectares (2,11%), 4686,7 hectares (38,91%), and 7107,08 hectares or 59% rispectively. Flood vulnerability is spread in entire village in Denpasar City with the varies level. It cause different physical condition area. Low vulnerability level up to medium is spread in North Denpasar Sub-District. High level vulnerability is spread in East Denpasar Sub-District and very high level vulnerability is distributed in West Denpasar and South Denpasar Sub-District.